Dynamic phenotypic correlates of social status and mating effort in male and female red junglefowl, Gallus gallus - Carleial, R; McDonald, GC; Pizzari, T (Wiley, 2019)
Despite widespread evidence that mating and intrasexual competition are costly, relatively little is known about how these costs dynamically change male and female phenotypes. Here, we test multiple hypotheses addressing this question in replicate flocks of red junglefowl (Gallus gallus). First, we test the interrelationships between social status, comb size (a fleshy ornament) and body mass at the onset of a mating trial. While comb size covaried positively with body mass across individuals of both sexes, comb size was positively related to social status in females but not in males. Second, we test for changes within individuals in body mass and comb size throughout the mating trial. Both body mass and comb size declined at the end of a trial in both sexes, suggesting that mating effort and exposure to the opposite sex are generally costly. Males lost more body mass if they (a) were socially subordinate, (b) were chased by other males or (c) mated frequently, indicating that subordinate status and mating are independently costly. Conversely, females lost more body mass if they were exposed to a higher frequency of coerced matings, suggesting costs associated with male sexual harassment and female resistance, although costs of mating per se could not be completely ruled out. Neither competitive nor mating interactions predicted comb size change in either sex. Collectively, these results support the notion that sex‐specific costs associated with social status and mating effort result in differential, sex‐specific dynamics of phenotypic change.